Spin polarized nodal loop state at Fermi level in the monolayer PrClS - Zhao, Yilin; Zhang, Li; Gao, Yufeng (Frontiers in Chemistry, 2025)
The investigation of two-dimensional materials exhibiting half-metallicity and topological features has become a rapidly growing area of interest, driven by their immense potential in nanoscale spintronics and quantum electronics. In this work, we present a comprehensive study of a two-dimensional PrClS monolayer, revealing its remarkable electronic and mechanical properties. Under its ferromagnetic ground state, the PrClS monolayer is shown to exhibit half-metallic behavior with 100% spin polarization originating from the spin-up channel. Of particular significance is the discovery of a spin-polarized nodal loop state within the spin-up channel. This intriguing state, characterized by a critical dispersion type and its precise alignment with the Fermi energy level, represents a feature of great interest for practical spintronic and quantum applications. Further analysis of the nodal loop topology using a maximally localized Wannier tight-binding Hamiltonian unveils distinct topological edge states. These edge states emerge clearly from the nodal loop crossings and are entirely separated from the bulk band projection, ensuring enhanced experimental detectability. The robustness of this nodal loop state is also explored under the influence of spin-orbit coupling, where it transforms into a unique hourglass-shaped dispersion while maintaining its fundamental characteristics, further solidifying its potential for experimental validation and deployment in advanced technologies. To assess the applicability of the PrClS monolayer in practical settings, its mechanical properties were thoroughly evaluated and several key parameters were analyzed, revealing significant mechanical anisotropy. This anisotropy underscores the importance of directional dependence in structural engineering and highlights the material’s versatility for applications requiring tailored mechanical responses. Overall, the PrClS monolayer represents an exceptional platform for investigating spin-polarized topological phenomena and demonstrates strong potential as an exciting material for both fundamental research and technological innovation.